Trichomes micromorphology and essential oil variation at different developmental stages of cultivated and wild growing Mentha pulegium L. populations from Portugal - Rodrigues, Leandra (2013)
The indumentum of Mentha pulegium L., studied by light and scanning electron microscopy, was characterized by non-glandular and glandular trichomes, which corresponded to the common arrangement described for the Lamiaceae family. Histochemistry revealed the presence of pectins, total lipids, acidic lipids and essential oils in the glandular trichomes secretions. The essential oil yield ranged from 0.3% (w/d.w.) in the vegetative phase to 1.6% at full flowering. Gas chromatography and gas chromatography–mass spectrometry essential oils composition analysis at full flowering revealed mostly quantitative rather than qualitative variations, with pulegone as the major compound (52–82%), followed by isomenthone (2–36%), menthone (0.1–17%), and piperitenone (1–15%). Comparative evaluation of cultivated and wild growing populations showed differences in the relative amounts of the main components of the essential oils isolated from plants harvested at different developmental stages.